Biogas‐producing microbial composition of an anaerobic digester and associated bovine residues - Carolina Senés‐Guerrero (MicrobiologyOpen, 2019)
Abstract Influenced by feedstock type and microbial inoculum, different microbial groups must precisely interact for high‐quality biogas yields. As a first approach for optimization, this study aimed to identify through time the biogas‐producing microbial community in a 10‐ton dry anaerobic digester treating cattle manure by denaturing gradient gel electrophoresis (DGGE) and metagenomics. Moreover, the associated bovine residues or feedstocks (leachate, manure, oxidation lagoon water, rumen) were also characterized to determine their contribution. A diverse and dynamic community characterized by Bacteria (82%–88%) and a considerable amount of Archaea (8%–15%) presented profiles particular to each stage of biogas production. Eukaryotes (2.6%–3.6%), mainly fungi, were a minor but stable component. Proteobacteria represented 47% of the community at the start of the run but only 18% at the end, opposite to the Bacteroidetes/Chlorobi group (8% and 20%, respectively), while Firmicutes (12%–18%) and Actinobacteria (12%–32%) remained relatively constant. Methanogens of the order Methanomicrobiales represented by several species of Methanoculleus were abundant at the end of the run (77%) contrary to Methanosarcinales (11%) and Methanobacteriales (0.7%). Therefore, methanogenesis mainly occurred by the hydrogenotrophic pathway. Manure and oxidation lagoon water seemed to contribute key microorganisms, while rumen dominated by Methanobrevibacter (72%) did not proliferate in the digester. Manure particularly possessed Methanoculleus (24%) and uncultured methanogens identified by DGGE, whereas oxidation lagoon was exclusively abundant in Methanolinea (18%) and Methanosaeta (19%). Leachate, as the microbial inoculum from a previous run, adequately preserved the biogas‐producing community. These results could lead to higher biogas yields through bioaugmentation strategies by incorporating higher proportions or an enriched inoculum from the relevant feedstocks.